(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to high sensing, computing and communication capabilities, the wireless sensor networks (WSNs) are widely used in different sectors, although with numerous resource constraints such as energy, processing power, storage and transmission range etc. The present study adopted the hybrid protocol integrating homogeneous and heterogeneous clustering protocols viz. Distributed Energy Efficient Clustering-maximum threshold (DEEC-MT) as compared with the basic DEEC, balanced and centralized DEEC (BC-DEEC) protocols. These three protocols were to enhance the energy efficiency and network lifetime of WSNs at different number of nodes (100 and 200) and packet size (3000 and 4000). The implementation of DEEC-MT protocol (number of nodes=200 and packet size=4000) resulted in increased lifetime of WSN by 19.8% over the BC-DEEC protocol. However, the corresponding increase was 37.6% over basic DEEC protocol. At 10000 rounds, the numbers of packets sent to the base station (BS) were 9.8 x 105 packets for DEEC-MT, while less than 1.7 x 105 packets for BC-DEEC and 2.3 x 105 packets for DEEC protocol. The reliability of DEEC-MT protocol was considerably higher by 24.7 and 13.8% as compared to basic DEEC and BC-DEEC protocols, respectively. The implementation of DEEC-MT protocol decreased the end-to-end delay by 23.7%, compared with BC-DEEC protocol. These results highlight that newly proposed DEEC-MT protocol was more energy efficient and had prolonged network lifetime.